Effect of Orange Peel Essential Oil and Thermotolerance Acquisition on Oxidative Stress Parameters of Liver, Heart and Spleen in Heat Stressed Japanese Quails - Dalkilic, Bestami; Ozcelik, Mehtap; Simsek, Ulku Gulcihan; Ciftci, Mehmet (Kafkas Univ, Veteriner Fakultesi Dergisi, 2015)
The aim of this study was to determine the effects of orange peel essential oil intake by feed and thermotolerance acquisition by early age treatments on antioxidant status of liver, heart and spleen in Japanese quails which subjected to acute heat stress. 168 seven-day-old quail chicks were randomly assigned to six groups as the control; thermal conditioning and fasting for 24 h fed with basal feed or 300 ppm orange peel essential oil added feed. Acute heat stress at marketing age was affected antioxidant systems of selected organs. Orange peel essential oil supplementation decreased Malondialdehyde (MDA) levels while no effect was observed on enzyme activities. Fasting and thermal conditioning at early age negatively affected the antioxidant status of selected organs. Orange peel essential oil may prevent tissues from lipid peroxidation and can be used as a natural antioxidant supplement in heat stress.
Portakal Kabuğu Esansiyel Yağı ve Termotolerans Kazandırmanın Sıcaklık Stresine Tabi Tutulan Japon Bıldırcınlarında Karaciğer, Kalp ve Dalakta Oksidatif Stres Parametrelerine Etkisi
Keywords: Antioxidant; Heat stress; Orange peel essential oil; Thermotolerance